Susceptibility to SLE in South Indian Tamils may be influenced by genetic selection pressure on TLR2 and TLR9 genes. Issue 1 (March 2015) - Devaraju, Panneer; Gulati, Reena; Antony, Paul T.; Mithun, C.B.; Negi, Vir S.
Highlights TLR2 gene remains monomorphic at position (G2408A) and failed to confer risk to develop SLE. Whereas the TLR9 gene has adapted the mutation for its enhanced expression thereby conferred a significant risk to develop SLE. Our findings suggests that the selection pressure exerted on these genes to combat the endemic infections turned out to be a genetic risk factor to develop autoimmune diseases like SLE.